Exponential Stability for Lamé System with Fractional Time-Varying and Boundary Feedback - Reda, S. Bousserhane; Memou, A.; Berkane, A.; zennir, Kh. (Discontinuity, Nonlinearity, and Complexity, 2026)
Due to the lack of effective research methods, the study of fractional time-varying and boundary feedback for Lamé system requires special studies and the involvement of new methods, so there are few works in this direction. The paper is devoted to Lamé system with fractional time-varying and boundary feedback. A general description of the question of well posedness of problem, their stability, and a review of the results are given. The novelty and main contributions located in the interaction between different damping terms and show the impact of each one of them on the stability.